2020
DOI: 10.3991/ijim.v14i09.11179
|View full text |Cite
|
Sign up to set email alerts
|

A Development of Augmented Reality Mobile Application to Promote the Traditional Indonesian Food

Abstract: Traditional food is a representation of the culture and identity of certain regions and is a symbol of cultural heritage. Traditional Indonesian food must be preserved and introduced to the community, especially the easy generation as the next generation of the nation as a form of love for the culture that has been passed down from generation to generation. It aims to avoid the influence of food or foreign cuisine that enters Indonesia, which from time to time makes the preservation of traditional Indonesian f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…According to the scientific literature review (Azuma, 1997;Billinghurst et al, 2015;Capuano et al, 2016;Cianciarulo, 2015;Dey et al, 2016;Wafa & Hashim, 2016;Weking et al, 2020), the most widely studied applications of augmented reality technology are manufacturing (automation), marketing and commerce, entertainment and game industry, education, arts, and culture sector (museums, libraries), fashion industry, medicine, military industry and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the scientific literature review (Azuma, 1997;Billinghurst et al, 2015;Capuano et al, 2016;Cianciarulo, 2015;Dey et al, 2016;Wafa & Hashim, 2016;Weking et al, 2020), the most widely studied applications of augmented reality technology are manufacturing (automation), marketing and commerce, entertainment and game industry, education, arts, and culture sector (museums, libraries), fashion industry, medicine, military industry and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To clarify, mobile applications are developed as a tool to support planning for going shopping. According to the review of related literatures and research, it was found that several applications have been developed to support online and on-site selling [11], [12], [13], [14], [15], [16], [17]. However, those applications still contains some limitations, i.e., they are unable to search for locations or navigate [11], [12], [14], and unable to record the data of searching for each type of products [16].…”
Section: Introductionmentioning
confidence: 99%
“…It means Indonesian people need to take action as soon as possible. Weking attempt to preserve traditional Indonesian food using Augmented Reality [2]. Their research shows that the application is helpful and very interactive to introduce traditional Indonesian food to the other community.…”
Section: Introductionmentioning
confidence: 99%